Improving a Low Axial Resolution Due to Improper Wavelength Calibration in Spectral-Domain Optical Coherence Tomography - Mengsi Zhang; Songjie Luo; Osami Sasaki; Ziyang Chen; Jixiong Pu (IEEE Photonics Journal, 2024)
Inaccurate wavelength calibration for spectral-domain optical coherence tomography (SD-OCT) generates a depth-dependent broadening of coherence peak. In this paper, a simple technique is proposed to eliminate the wavelength calibration error by the spectral-resolved interference signal correction. Utilizing the nonlinear component of phase distribution in wavenumber domain and the optimization algorithm, an optimized coefficient is obtained and used to improve the axial resolution. The simulation was carried out to verify the principle of the proposed method. In experiment, a sample of reflecting mirror was used to obtain the nonlinear phase and the optimized coefficient for correcting the spectral-resolved interference signals of tapes and chicken breast. In the measurement of a layer of tape with a thickness of about 1.5 mm, two full width half maximum (FWHM) of amplitude generated from the front and rear surfaces dropped to 7.73 μm and 9.99 μm from 33.57 μm and 55.36 μm after the signal correction. A self-made sample containing 6 layers of tape and a part of chicken breast were tested, whose sharpness metric grow larger than 12.8% after signal correction. This method provides a simple way to improve the image quality of SD-OCT in improper wavelength calibration.